Mechanisms of Tolerance Induction by Dendritic Cells In Vivo - Hasegawa, Hitoshi; Matsumoto, Takuya (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are a heterogeneous population playing a pivotal role in immune responses and tolerance. DCs promote immune tolerance by participating in the negative selection of autoreactive T cells in the thymus. Furthermore, to eliminate autoreactive T cells that have escaped thymic deletion, DCs also induce immune tolerance in the periphery through various mechanisms. Breakdown of these functions leads to autoimmune diseases. Moreover, DCs play a critical role in maintenance of homeostasis in body organs, especially the skin and intestine. In this review, we focus on recent developments in our understanding of the mechanisms of tolerance induction by DCs in the body.